Are Sexual Minority Stressors Associated with Young Men who Have Sex with Men's (YMSM) Level of Engagement in PrEP?. Issue 3 (3rd July 2021) - Meanley, Steven; Chandler, Cristian; Jaiswal, Jessica; Flores, Dalmacio D.; Stevens, Robin; Connochie, Daniel; Bauermeister, José A.
Abstract: Sexual minority stressors (community homophobia, sexuality-related discrimination, and internalized homonegativity) are negatively associated with accessing HIV prevention services among men who have sex with men (MSM). Few studies have tested minority stressors' associations with PrEP engagement among high-HIV risk young MSM (YMSM). Therefore, we assessed the associations between PrEP-indicated YMSM's progression along the PrEP continuum and their experiences of minority stress. N  = 229 YMSM completed a web-survey on PrEP-related behaviors and minority stress. Adjusted for covariates, we developed two partial-proportional odds models examining the associations between PrEP continuum progression and minority stressors, as a composite, and community homophobia, sexuality-related discrimination, and internalized homonegativity, respectively. Our multivariable model demonstrated minority stress levels to be negatively associated with PrEP continuum location ( AOR  = 0.76, 95% CI: 0.58–0.99). Broken down, discrimination was positively associated with reporting being at an advanced location along the continuum ( AOR  = 1.39, 95% CI: 1.06–1.82). Internalized homonegativity was negatively associated with continuum location between PrEP-aware participants with no intention to initiate and participants who intended to initiate PrEP ( AOR  = 0.45, 95% CI: 0.27–0.77) and between those who intended to initiate and those who had ever used PrEP ( AOR  = 0.39, 95% CI: 0.22–0.69). Our findings suggest that minority stress, especially internalized homonegativity, remains a barrier to PrEP among PrEP-indicated YMSM. Sexuality-related discrimination was associated with PrEP continuum progression, suggesting potentially well-developed, adaptive coping skills (e.g., ability to locate sexuality-affirming providers). Coupled with stigma reduction efforts, HIV prevention services aiming to promote PrEP should incorporate internalized homonegativity screenings and referrals into sexuality-affirming resources for PrEP-indicated YMSM.